An assessment of the influence of Christian faith on art adherence for Christians living with HIV at ZNNP+ Gweru urban - Moyo, Sibongile (Midlands State University, 2018)
The study aim was to assess the influence of Christian faith on ART adherence by persons living with HIV subscribing to Christianity as their religion and enrolled in the Zimbabwe National Network of People living with HIV Gweru. The research was necessitated by the observation of the rise in Christian denominations that were found to be preaching the gospel of healing from HIV, alongside the presented statistics on the AIDS-related deaths and HIV prevalence rates within the district. The approach employed in the research was qualitative, taking on an exploratory nature, seeing that the area of assessing the respective impact of Christian faith on ART within the district, had been under-studied. Participants for the research were identified in a single-stage sampling procedure, through selecting them from an existent organizational database of the support groups in which the participants were enrolled. Data was analysed thematically, with demographics being interpreted and presented in a tabulated manner. The main findings of the research were that within the first year of being initiated on the ART program, participants tended to lean towards Christian faith as a source of consolation, in disbelief of their sero-status. As such, the church teachings and attitudes of persons surrounding them from the church system often discouraged them from taking ART. However, with time, following acceptance of their sero-status, Christians living with HIV were able to adhere better to their medication basing on the belief that God cared for them and wanted them to live long. As such, the conclusions drawn from the research were that Christian faith positively impacts adherence for persons living with HIV, only after the people in question would have managed to get through the factors that affect adherence for every other person on the ART program, such as disclosure, status acceptance and knowledge of ART.